The human factor of cybercrime - Leukfeldt, E. R.; Holt, Thomas J. 1978- (Routledge, 2020)
"This book focuses on the human factor in cybercrime: its offenders, victims and parties involved in tackling cybercrime. It brings together leading criminologists from around the world to consider questions about the nature of of cybercrime, and examines all facets of victimization, offending, offender networks, and policy responses"--